The Islamization of English literary studies: a postcolonial approach - Hasan, Md. Mahmudul (The International Institute of Islamic Thought, 2013)
In today’s world where the former colonized are reshaping their relation with the colonizer, the concept of decolonizing or indigenizing education is widely discussed in postcolonial studies. Decolonizing/indigenizing education counters the western systems of knowledge’s hegemony over those of non-western systems of thought and requires the development of a new approach to education that keeps in view the indigenous societies’ socio-cultural and religious values and traditions. The Islamization of Knowledge undertaking maintains a similar approach, but additionally requires an Islamic perspective on knowledge. Among all western disciplines, English literature is arguably the most culturally charged and carries western value-laden ideas. This reality points to the need to look at it from Islamic perspectives. Based on this theoretical concept, this study seeks to establish the urgency and feasibility of Islamizing English (British) literary studies.